2004
DOI: 10.1088/0957-4484/15/9/027
|View full text |Cite
|
Sign up to set email alerts
|

Sol–solvothermal synthesis and microwave evolution of La(OH)3nanorods to La2O3nanorods

Abstract: Solvothermal synthesis of La(OH)3 sol and microwave radiation drying of La(OH)3 nanorods were employed for the first time to synthesize La2O3 nanorods with diameters around 10 nm and lengths up to 200 nm. The resulting products were characterized with XRD, TEM and HRTEM. Microwave radiation drying was found to be more effective to maintain the morphologies of nanorods than conventional drying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 20 publications
2
66
1
Order By: Relevance
“…One-dimensional lanthanide hydroxides (La(OH) 3 ) have been of growing interest owing to their promising applications in sensors, 6 catalysts, 7,8 and capacitors. 9 Various synthesis techniques have been adopted for the preparation of La(OH) 3 nanostructures, including solvothermal, 10 hydrothermal, 11,12 precipitation, 13 and composite-hydroxide-mediated (CHM) methods. 6 However, these preparation methods generally need the use of surfactants/templates or complicated reaction conditions to get the desired shape/structure.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional lanthanide hydroxides (La(OH) 3 ) have been of growing interest owing to their promising applications in sensors, 6 catalysts, 7,8 and capacitors. 9 Various synthesis techniques have been adopted for the preparation of La(OH) 3 nanostructures, including solvothermal, 10 hydrothermal, 11,12 precipitation, 13 and composite-hydroxide-mediated (CHM) methods. 6 However, these preparation methods generally need the use of surfactants/templates or complicated reaction conditions to get the desired shape/structure.…”
Section: Introductionmentioning
confidence: 99%
“…Although many methods have been developed for the synthesis of lanthanum nanostructures including hydrothermal [25], solvothermal [26], micro emulsion or reverse micelles [27], sol gel [28], laser deposition [29] and other chemical and physical methods; some of these methods are affected by long reaction time, high temperature, high pressure, expensive surface materials (surfactant) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in a solvothermal system, the crystal growth can be controlled and products with di®erent morphologies can be gained. [31][32][33][34][35] Tian et al reported a modi¯ed liquid-solid solution solvothermal strategy for synthesizing Mn 2þ -doped NaYF 4 :Yb/Er nanoparticles, which possess the rational manipulation of red and green upconversion luminescence, and the pure dark red emission (650-670 nm). 36 …”
Section: Ucl Mechanism Of the Lanthanidedoped Nanophosphorsmentioning
confidence: 99%